Modeling and simulation tools in mechanical design education: what didactical determinants? - et. al., Youssoupha GUEYE, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article presents the results of a study on the integration of modeling and simulation tools in the teaching of mechanical design. Indeed, optimisation of the design process often uses modelling and simulation tools in mechanical design activities. Thus, to meet the needs of the labour market, training situations in this field we use communication and information technology. In particular, digital tools are used for the development of virtual models intended for sizing and optimisation, and/or validating the behaviour and performance of a system, component, or process. However, their use in the teaching–learning activities of mechanical design give rise to many problems. These problems are often related to the educational use of these tools; the ergonomics of their interfaces and the didactic interaction. Thus, this study proposes in the framework of mechanical design teaching, through a case study, to analyze determinants of the didactic activity of the teacher in order to identify the contingencies of the didactic action. It presents didactic determinants on the process of teaching mechanical design using modeling and simulation tools.